The harmonic and sideband structure of the kilohertz quasi-periodic oscillations in Sco X-1 - Méndez, Mariano R. (2000)
We use data from the Rossi X-ray Timing Explorer to search for harmonics and sidebands of the two simultaneous kilohertz quasi-periodic oscillations (kHz QPOs) in Sco X-1. We do not detect any of these harmonics or sidebands, with 95 per cent confidence upper limits to their power between ∼1 and ∼10 per cent of the power of the upper kHz QPO. The oscillations produced at these frequencies may be attenuated in a scattering corona around the neutron star. We find that upper limits to the unattenuated power of some of the strongest theoretically predicted harmonics and sidebands are as low as ∼2per cent of the unattenuated power of the high-frequency QPO in Sco X-1.